Вивчення можливостей оптимізації uv розгорток для подальшого текстурування у програмі «maya» - Дякуненко, Д. (My University, 2020)
Nowadays many programs and software utensils can de used for the creation of UV developed views and optimal UV maps for further texturization. The investigation in the area of the methods of optimizing the creation of UV maps were carried out. In order to prevent the formation of artifacts and other nuisances, a simple and effective method was chosen to achieve the desired result in a few steps
Keywords: uv розгортки; текстурування